Arsenic sorption on zero-valent iron-biochar complexes. (15th June 2018) - Bakshi, Santanu; Banik, Chumki; Rathke, Samuel J.; Laird, David A.
Abstract: Arsenic (As) is toxic to human and is often found in drinking water in India and Bangladesh, due to the natural abundance of arsenides ores. Different removal procedures such as precipitation, sorption, ion exchange and membrane separation have been employed for removal of As from contaminated drinking water (CDW), however, there is a critical need for low-cost economically viable biochar modification methods which can enhance As sorption. Here we studied the effectiveness of zero-valent iron (ZVI)-biochar complexes produced by high temperature pyrolysis of biomass and magnetite for removing As 5+ from CDW. Batch equilibration and column leaching studies show that ZVI-biochar complexes are effective for removing As 5+ from CDW for the studied pH range (pH ∼7–7.5) and in the presence of competing ions. XPS As 3d analysis of ZVI-biochar complexes exposed to As 5+ in the batch and column studies show primarily As 3+, indicating simultaneous oxidation of Fe° to Fe 3+ and reduction of As 5+ to As 3+ . SEM-EDS and XRD analyses show isomorphous substitution of As 3+ for Fe 3+ in neo-formed α/γ-FeOOH on biochar surfaces, which is attribute to co-precipitation. This study also demonstrates the efficacy of pyrolyzing biomass with low-cost iron ores at 900 °C to rapidly produce ZVI-biochar complexes, which have potential to be used for treatment of As CDW. Graphical abstract: Highlights: Zero-valent iron (ZVI) biochar complexes are effective for As 5+ removal from water. Co-pyrolysis of low cost iron ore and biomass can produce ZVI biochar complexes. Simultaneous oxidation of Fe° to Fe 3+ and reduction of As 5+ to As 3+ occurred. As 3+ sorption attributed to isomorphous substitution of As 3+ for Fe 3+ in α/γ-FeOOH. ZVI-biochar complex developed in this study can mitigate As contamination risk.